2017
DOI: 10.1097/shk.0000000000000823
|View full text |Cite
|
Sign up to set email alerts
|

Microparticles from Patients Undergoing Percutaneous Coronary Intervention Impair Vasodilatation by Uncoupling Endothelial Nitric Oxide Synthase

Abstract: PCI further enhances the vascular injury effect of MPs. Circulating MPs may be a potential therapeutic target for patients undergoing PCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Furthermore, MVs of endothelial origin have shown to decrease nitric oxide (NO) production in vitro ( 22 , 23 ) and under high glucose conditions through changes in oxidative stress ( 24 ) or inducing a temporal cross talk between mitochondria and endoplasmic reticulum ( 25 ). These effects have been obtained in ex vivo studies ( 23 , 26 ) and with patient-derived MVs in pathologies such as myocardial infarction (MI) ( 27 ), end-stage renal failure ( 15 ), metabolic syndrome ( 28 ), valvular heart disease and cardiac injury ( 29 ), and undergoing percutaneous coronary intervention ( 30 ). As a result, vascular tone and endothelial repair capacity are altered.…”
Section: Mv-mediated Regulatory Mechanisms In the Development And Promentioning
confidence: 99%
“…Furthermore, MVs of endothelial origin have shown to decrease nitric oxide (NO) production in vitro ( 22 , 23 ) and under high glucose conditions through changes in oxidative stress ( 24 ) or inducing a temporal cross talk between mitochondria and endoplasmic reticulum ( 25 ). These effects have been obtained in ex vivo studies ( 23 , 26 ) and with patient-derived MVs in pathologies such as myocardial infarction (MI) ( 27 ), end-stage renal failure ( 15 ), metabolic syndrome ( 28 ), valvular heart disease and cardiac injury ( 29 ), and undergoing percutaneous coronary intervention ( 30 ). As a result, vascular tone and endothelial repair capacity are altered.…”
Section: Mv-mediated Regulatory Mechanisms In the Development And Promentioning
confidence: 99%
“…For EMPs, Jimenez et al [35] showed that when apoptosis was induced in endothelial cells in-vitro, activation markers on the endothelial cells and cell activation induced CD62E+ EMPs remained stable, while apoptotic markers and the production of apoptotic EMPs increased rapidly. In patients with acute coronary syndrome, three studies have documented a pattern with high concentrations of apoptotic EMPs [35, 55, 56], probably reflecting acute endothelial cell injury due to ischemia, whereas other MP subtypes were not described.…”
Section: Discussionmentioning
confidence: 99%
“…The level of PMVs was positively associated with the extent of myocardial damage (peak CK-MB: r = 0.408, p = 0.019). Ye et al (2017)…”
Section: Pmvs)mentioning
confidence: 99%
“…For their role in regulating the coagulation cascade and thromboinflammation, identifying circulating PMVs might have a role in stratifying patients at risk of AMI in both primary and secondary prevention setting. High serum levels of circulatory PMVs have been observed in patients with ACS and are also associated with the degree of elevation of cardiac enzymes, inflammatory biomarkers and various markers of myocardial injury(Christersson, Thulin, & Siegbahn, 2017;Cui et al, 2013;Giannopoulos et al, 2014;Hartopo, Puspitawati, Gharini, & Setianto, 2016; Montoro-Garcia et al, 2013;Ye et al, 2017;Table 1)…”
mentioning
confidence: 99%